2015
DOI: 10.5194/aab-58-57-2015
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the genetic distances of bovids and cervids using BovineSNP50k BeadChip

Abstract: Abstract. This study presents the application of BovineSNP50 BeadChip for genome-wide screening of two taurine breeds (Bos primigenius taurus) and Zebu (Bos primigenius indicus), and two species from the family Cervidae: red deer (Cervus elaphus) and fallow deer (Dama dama). The aim of the paper was to evaluate the use of bovine array for cross-species genotyping and analyse single nucleotide polymorphism (SNP) distribution, diversity within groups of animals and genetic distance among analysed species. The nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…They found that 38.7 % of loci could be genotyped, of which 5 % (n = 1068) were polymorphic. R. Kasarda et al [37] performed the study of two species from the family Cervidae: red deer (Cervus elaphus) and fallow deer (Dama dama). In total, 94.76 % SNPs were successfully genotyped and 5.24 % (1542) of them were polymorphic.…”
Section: Differentiation Of the Studied Breeds Of Reindeermentioning
confidence: 99%
See 2 more Smart Citations
“…They found that 38.7 % of loci could be genotyped, of which 5 % (n = 1068) were polymorphic. R. Kasarda et al [37] performed the study of two species from the family Cervidae: red deer (Cervus elaphus) and fallow deer (Dama dama). In total, 94.76 % SNPs were successfully genotyped and 5.24 % (1542) of them were polymorphic.…”
Section: Differentiation Of the Studied Breeds Of Reindeermentioning
confidence: 99%
“…For non-model species (including reindeer), due to the lack of information about the complete genomes, the development of such kind of an SNP matrix remains unachievable [31]. However, a number of authors have demonstrated the possibility of using such commercial DNA chip (designed for domestic animals) for obtaining information about the genetic diversity and population structure of non-model species [32][33][34][35][36][37]. In 2015, we published the first evidence of the successful application of DNA chips developed for cattle (Illumina Bo-vineSNP50 BeadChip) and domestic sheep (Illumina OvineSNP50 BeadChip) to study the reindeer [38].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The final data set comprised 8357 SNPs for domestic and 8145 SNPs for wild individuals. Kasarda et al [30], using 5.3% polymorphic SNPs from the BovineSNP50 BeadChip, successfully evaluated genetic diversity and genetic relatedness among three groups of cervids. Genetic differences between farmed and free-range Red deer originating from Slovakia were observed based on 1530 polymorphic markers [48].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the abundance of scientific work on the genetic biodiversity of the Cervidae family members through commercial SNP genotyping arrays [4,[29][30][31][32]-including our previous study, which attempted to determine the differences among the domestic reindeer groups within the Nenets Autonomous district, the Murmansk region, and Yakutia, as well as among wild tundra and taiga forms inhabiting Yakutia and western Taymyr-information on the genetic structure and diversity of all domestic reindeer breeds inhabiting the Russian Far North is still lacking.…”
mentioning
confidence: 99%